NAIL PLATE MICROBIOLOGY AND THE EFFECT OF NAIL PROCEDURES ON THE SKIN BARRIER - Liudmila Yukhymchak (Scholars Digest Publishing, 2024)
This paper summarizes current data on the microbiology of the nail apparatus from the perspective of molecular research and examines the main mechanisms of damage to the skin barrier during nail procedures, including cuticle microtrauma, lipid extraction with solvents, allergic sensitization to (meth) acrylates, occlusion, and the photobiological effects of UV/LED devices. It is shown that barrier deficiency of the periungual skin creates conditions for microbial dysbiosis, maintenance of chronic inflammation, and the formation of mixed infections of the nail apparatus. The integration of microbiological and dermatophysiological data emphasizes the need for a comprehensive approach to the prevention and treatment of nail diseases, including maintaining the integrity of the skin barrier, reducing trauma. nail procedures and taking into account the polymicrobial nature of nail lesions.
Keywords: Nail plate, microbiome, onychomycosis, paronychia, Pseudomonas, (meth) acrylates, TEWL, skin barrier, acetone, UV lamps.